1993
DOI: 10.2105/ajph.83.11.1625
|View full text |Cite
|
Sign up to set email alerts
|

Activity, inactivity, and obesity: racial, ethnic, and age differences among schoolgirls.

Abstract: IntdudionAlthough studies have explored the frequency' and determinants2 of children's participation in physical activities, racial/ethnic and age differences (elementaly to high school) in activity levels have not been studied; also, the relationship between physical activity, sedentary behavior, and the prevalence of obesity in different racial/ethnic and age groups has not been examined. This study explored race-, ethnicity-, and age-related differences in activity, inactivity, and obesity among a multiraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
5

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 8 publications
5
72
0
5
Order By: Relevance
“…6,11,13,14 The association was, however, dependent on the assessment tool, because physical activity levels obtained from the prospective 3-day activity record were not related to overweight. Because the recording is based on subjective evaluation of the intensity of daily activities, an overestimation of activity intensity by overweight children could mask a true association between activity and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,11,13,14 The association was, however, dependent on the assessment tool, because physical activity levels obtained from the prospective 3-day activity record were not related to overweight. Because the recording is based on subjective evaluation of the intensity of daily activities, an overestimation of activity intensity by overweight children could mask a true association between activity and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies have shown a positive association between the time spent watching television and obesity in children, 4 ± 10 whereas other reports have failed to ®nd a relation. 11 ± 13 The association between children's vigorous or total physical activity and obesity is also inconsistent: some studies reported an inverse relation, 6,11,13,14 while some researchers did not ®nd an association. 7,9,10 The amount and kind of physical activity in children are modi®ed by physiological, biomechanical and social factors.…”
Section: Introductionmentioning
confidence: 99%
“…A moderator analysis of the relationship between video/ computer game use and body fatness was not performed because second-order sampling error is likely to confound results when the initial number of effects is small. 7 TV viewing, video/computer game use and physical activity In total, 33 studies [11][12][13]17,18,21,25,[30][31][32]36,38,39,46,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] were located that presented a measure of association between physical activity and TV viewing, playing video games or computer use. Nine studies were excluded from analyses either because they had serious design limitations, 46,50,51 presented insufficient data for meta-analytic synthesis, 11,12,54 presented data on composite measures of sedentary behavior 49,52 or reported on special populations.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Body fatness was usually assessed using skinfold thickness (60%) or BMI (37%) derived from direct observation of height and weight. Four samples 15,20,38 relied on self-reported height and weight to compute BMI. Only one sample used dualenergy X-ray absorptiometry (DXA), 35 which is considered a 'gold standard' technique for assessing fat mass in children.…”
Section: Assessment Of Body Fatnessmentioning
confidence: 99%
“…89 Such null findings are also common. 40,57,90,91 We found two case-control studies in our review of the literature, which were essentially crosssectional in design. Television was significantly related to obesity in a case-control study of 223 obese 7-10-y-old children and controls in Sao Paulo.…”
Section: Physical Inactivity and The Development Of Obesitymentioning
confidence: 99%